1992
DOI: 10.1002/ana.410310607
|View full text |Cite
|
Sign up to set email alerts
|

Differences in sensitivity to hyperglycemic hypoxia of isolated rat sensory and motor nerve fibers

Abstract: We explore whether the prevalence of sensory deficits in diabetic neuropathy can be explained by diffuse endoneurial hypoxia. Isolated ventral and dorsal rat spinal roots incubated in 2.5 or 25 mM extracellular glucose were transiently exposed to hypoxia (30 min) in a solution of low buffering power. Compound nerve action potentials and extracellular direct current potentials were continuously recorded before, during, and after hypoxia. In both ventral and dorsal roots incubated in 2.5 mM glucose, sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…Resistance to hypoxia and liability to hypoxia-related electrophysiological damage have been observed previously in isolated peripheral nerves exposed to hyperglycemic hypoxia (21)(22)(23). The following experiments were designed in view of two observations made in these studies.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Resistance to hypoxia and liability to hypoxia-related electrophysiological damage have been observed previously in isolated peripheral nerves exposed to hyperglycemic hypoxia (21)(22)(23). The following experiments were designed in view of two observations made in these studies.…”
Section: Resultsmentioning
confidence: 94%
“…Previously, we have shown that a preincubation period of 30 min to ~6 h in 2.5 mM D-glucose resulted in a uniform response to hypoxia. The altered sensitivity to hypoxia in high concentrations of D-glucose, on the other hand, required at least 2 h of preincubation (23). Therefore, except in experiments with normoglycemic hypoxia, spinal roots in this study were preincubated for 3-6 h in different hexose-containing solutions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one exposure to hypoxia was performed on each rat dorsal spinal root and therefore a standardized experimental protocol was used for comparison of data obtained from different spinal roots (we restricted this study to dorsal roots, since sensory fibres are more readily damaged by hyperglycaemic hypoxia 9 ). This protocol included the registration of the peak height in compound action potentials for 10 min before hypoxia, during the exposure to hypoxia (30 min), and during the period after re-oxygenation (another 35 min).…”
Section: Resultsmentioning
confidence: 99%